RISK ANALYSIS OF MUSYARAKAH FINANCING AT BANK ACEH SYARIAH, INDONESIA - Tazkia Al Munawar (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2025)
Musyarakah financing is one form of sharia-based financing applied by Islamic financial institutions, including Bank Aceh Syariah. This article aims to identify the risks in the musyarakah financing scheme. This research uses an empirical juridical approach with a descriptive qualitative method. Data were obtained through interviews with Bank Aceh Syari’ah employees and analysis of related documents. The results showed that Bank Aceh Syari’ah implemented risk management policies by periodically assessing customer eligibility and monitoring financing. However, there are obstacles in implementation, such as low customer interest in profit-sharing schemes and a lack of understanding of musyarakah contracts. This study suggests increasing socialisation and Islamic financial literacy in the community and strengthening risk mitigation policies to improve the effectiveness of musyarakah financing at Bank Aceh Syari’ah.